How do you solve the equation 3(2x - 4) = 2x + 8?
HOME > > How do you solve the equation 3(2x - 4) = 2x + 8?

# How do you solve the equation 3(2x - 4) = 2x + 8?

[From: ] [author: ] [Date: 17-07-06] [Hit: ]
How do you solve the equation 3(2x - 4) = 2x + 8?
I've been trying to work this out for a while now and I've been struggling to find decent examples on the internet that show how to do this question. Also, what is the name of this topic so in future I can look in my revision book? Thank you!
-------------------------------------------------------

Paul say: 3(2x-4) means 3 multiplied by all of 2x-4 so multiply the 2x by 3 and multiply the -4 by 3.

3(2x-4) = 6x - 12

6x-12 = 2x+8

now gather like terms.

6x - 2x = 8+12 (note how the sign changes as the terms cross the = sign)

4x = 20 (like terms can be combined)

x = 5 (the value for x is revealed by dividing both sides by 4)

These videos might help.

-
say: x=5
-
Shelby say: Simplifying
3(2x + 4) = 2x + -8

Reorder the terms:
3(4 + 2x) = 2x + -8
(4 * 3 + 2x * 3) = 2x + -8
(12 + 6x) = 2x + -8

Reorder the terms:
12 + 6x = -8 + 2x

Solving
12 + 6x = -8 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
12 + 6x + -2x = -8 + 2x + -2x

Combine like terms: 6x + -2x = 4x
12 + 4x = -8 + 2x + -2x

Combine like terms: 2x + -2x = 0
12 + 4x = -8 + 0
12 + 4x = -8

Add '-12' to each side of the equation.
12 + -12 + 4x = -8 + -12

Combine like terms: 12 + -12 = 0
0 + 4x = -8 + -12
4x = -8 + -12

Combine like terms: -8 + -12 = -20
4x = -20

Divide each side by '4'.
x = -5

Simplifying
x = -5
-
Brainard say: 3(2x - 4) = 2x + 8
12
keywords: solve,you,equation,the,How,do,How do you solve the equation 3(2x - 4) = 2x + 8?
New
Hot
© 2008-2010 http://www.science-mathematics.com . Program by zplan cms. Theme by wukong .